Antibacterial Activity Test of Ganitri (Elaeocarpus ganitrus Roxb.) Leaf Methanol Extract against Bacteria (Propionibacterium acne) - Titi Pudji Rahayu; Naelaz Zukhruf Wakhidatul Kiromah; Nindi Dwi Agustina (Urecol Journal. Part D: Applied Sciences, 2021)
Ganitri plant (Elaeocarpus ganitrus Roxb.) is one type of plant that can be discovered in several countries, such as Indonesia. This plant has a number of benefits as it contains flavonoid, tannins, phenolics, alkaloids, along with triterpenoids. In addition, that plant has significant role to decrease microbial activities including Staphylococcus aureus, Bacillus cereus, Candida albicans and Penicillium sp. These activities consist of three stages as follows inhibiting nucleic acid synthesis, then followed by hampering cell membrane function and finally decreasing bacterial energy metabolism. The mechanism denatures cell proteins leading an imbalance of molecules, ions and cell lysis as well. Extraction process has been completed by maceration method of 3-kg-wet leaves, a 1-kg-dry simplicial, a 500-g macerated simplicial mixed with 5 L methanol solvent and 33.33 % of simplicial, and 95.08 g of yield extract with 19.01%. Its process generated green color extract having bitter taste and thick form, 0.5% of water, 15.9% of ash, and 0.4% of insoluble acid. Identification of these active ingredients that using positive phytochemical resulted flavonoids. TLC (Thin-layer chromatography) test was used with 0.75 of positive control quercetin and 0.81 of flavonoid extract. Antibacterial activity testing was applied by calculating the inhibitory power of Nutrient Agar with negative control using sterile water. Afterwards, implemented a positive control using clindamycin resulted of several concentration as follows of 10 % (10.6), 20% (10.6), 30% (9.25), 40% (10.12), 50% (9.37) and 100% (38.75).